Yoga in schools that contributes to a positive classroom atmosphere for young children and educators: a PRISMA scoping review - Martin, Beverley; Peck, Blake; Terry, Daniel (Frontiers in Education, 2024)
Introduction: This scoping review aims to examines yoga taught to children in a variety of different educational settings including after-school and in-school activity. Yoga has been found to support children in regard to wellbeing in a number of ways.Methods: A scoping review using a systematic approach was undertaken using EBSCO, CINAHL, Medline and Psycinfo. Google Scholar was used to search for grey literature and journal reference lists reviewed.Results: Fourteen studies were identified within the review that describe how children are able to understand and regulate their bodies through movement. As such four main themes were identified and included: (1) yoga and psychological wellbeing in school children; (2) yoga and self-regulation in pre-school children (3) yoga and cognitive function in school children; and (4) yoga and contemplative practices.Children who participate in yoga during and after school were framing their world using their own creativity and fantasy in an attempt to understand and navigate it. The physical and psychological difficulty of some of the yoga shapes assisted children to develop a persistent mindset which enabled them to use in other unrelated contexts, such as difficulties at school.